Microglial priming of antigen presentation and adaptive stimulation in Alzheimer's disease - Das, Rashmi; Chinnathambi, Subashchandrabose (Cellular and Molecular Life Sciences, 2019)
The prominent pathological consequences of Alzheimer's disease (AD) are the misfolding and mis-sorting of two cellular proteins, amyloid-beta and microtubule-associated protein Tau. The accumulation of toxic phosphorylated Tau inside the neurons induces the increased processing of amyloid-beta-associated signaling cascade and vice versa. Neuroinflammation-driven synaptic depletion and cognitive decline are substantiated by the cross talk of activated microglia and astroglia, leading to neuron degeneration. Microglia are the brain-resident immune effectors that prove their diverse functions in maintaining CNS homeostasis via collaboration with astrocytes and T lymphocytes. Age-related senescence and chronic inflammation activate microglia with increased pro-inflammatory markers, oxidative damage and phagocytosis. But the improper processing of misfolded protein via lysosomal pathway destines the spreading of 'seed' constituents to the nearby healthy neurons. Primed microglia process and present self-antigen such as amyloid-beta and modified Tau to the infiltrated T lymphocytes through MHC I/II molecules. After an effective conversation with CD4(+) T cells, microglial phenotype can be altered from pro-active M1 to neuro-protective M2 type, which corresponds to the tissue remodeling and homeostasis. In this review, we are focusing on the change in functionality of microglia from innate to adaptive immune response in the context of neuroprotection, which may help in the search of novel immune therapy in AD.

Actin-mediated microglial chemotaxis via G-protein coupled purinergic receptor in alzheimer's disease - Das, Rashmi; Chinnathambi, Subashchandrabose (Neuroscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease mainly associated with aging, oxidative stress and genetic mutations. There are two pathological proteins involved in AD; Amyloid-beta peptide and microtubule-associated protein Tau (MAPT). The beta- and gamma-secretase enzyme cleaves the Amyloid precursor protein, which results in the formation of extracellular plaques in brain. While, Tau undergoes hyperphosphorylation and other post-translational modifications (PTMs), which eventually generates Tau oligomers, and intracellular neurofibrillary tangles (NFTs) in neurons. Moreover, the brain-resident glia and infiltrated macrophages elevate the level of CNS inflammation, which trigger the oxidative damage of neuronal circuits by reactive oxygen species (ROS) and Nitric oxide (NO). Microglia is the primary immune cell in the CNS, which is continuously surveilling the neuronal synapses and pathogen invasion. Microglia in the resting state is called `Ramified', which possess long surveilling extensions with a small cell body. But, upon activation, microglia retracts the cellular extensions and transform into round migratory cells, called as `Amoeboid' state. Activated microglia undergoes actin remodeling by forming lamellipodia and filopodia, which directs the migratory axis while podosomes formed are involved in extracellular matrix degradation for invasion. Protein-aggregates in malfunctioning synapses and in CNS milieu can be detected by microglia, which results in its activation and migration. Subsequently, the phagocytosis of synapses leads to the inflammatory burst and memory loss. The extracellular nucleotides released from damaged neurons and the cytokine-chemokine gradients allow the neighboring microglia and macrophages to migrate-infiltrate at the site of neuronal-damage. The ionotropic (P2XR) and metabotropic (P2YR) purinergic receptor recognize extracellular ATP/ADP, which propagates through the intracellular calcium signaling, chemotaxis, phagocytosis and inflammation. The P2Y receptors give `find me' or `eat me' signals to microglia to either migrate or phagocytose cellular debris. Further, the actin cytoskeleton helps microglia to mediate directed chemotaxis and neuronal repair during neurodegeneration. Hence, we aim to emphasize the connection between purinergic signaling and actin-driven mechanical movements of microglia for migration and inflammation in AD. (C) 2020 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: actin remodeling; Alzheimer's disease; microglia; P2Y signaling; purinergic GPCRs; Tauopathy

Basic limonoid modulates chaperone-mediated proteostasis and dissolve Tau fibrils - Gorantla, Nalini Vijay; Das, Rashmi; Chidambaram, Hariharakrishnan; Dubey, Tushar; Mulani, Fayaj A.; Thulasiram, V. Hirekodathakallu; Chinnathambi, Subashchandrabose (Scientific Reports, 2020)
The Alzheimer's disease pathology is associated with accumulation of intracellular neurofibrillary tangles and extracellular senile plaques. The formation of initial nucleus triggers conformational changes in Tau and leads to its deposition. Hence, there is a need to eliminate these toxic proteins for proper functioning of neuronal cells. In this aspect, we screened the effect of basic limonoids such as gedunin, epoxyazadiradione, azadirone and azadiradione on inhibiting Tau aggregation as well as disintegration of induced Tau aggregates. It was observed that these basic limonoids effectively prevented aggregates formation by Tau and also exhibited the property of destabilizing matured Tau aggregates. The molecular docking analysis suggests that the basic limonoids interact with hexapeptide regions of aggregated Tau. Although these limonoids caused the conformational changes in Tau to beta-sheet structure, the cytological studies indicate that basic limonoids rescued cell death. The dual role of limonoids in Tau aggregation inhibition and disintegration of matured aggregates suggests them to be potent molecules in overcoming Tau pathology. Further, their origin from a medicinally important plant neem, which known to possess remarkable biological activities was also found to play protective role in HEK293T cells. Basic limonoids were non-toxic to HEK293T cells and also aided in activation of HSF1 by inducing its accumulation in nucleus. Western blotting and immunofluorescence studies showed that HSF1 in downstream increased the transcription of Hsp70 thus, aggravating cytosolic Hsp70 levels that can channel clearance of aberrant Tau. All these results mark basic limonoids as potential therapeutic natural products.

Effect of melatonin on tau aggregation and tau-mediated cell surface morphology - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Aggregation of Microtubule-associated protein Tau and its deposition in the form of neurofibrillary tangles (NFTs) is one of the pathological hallmarks of Alzheimer's disease (AD). Tau aggregation inhibition has been targeted in various studies including natural compounds and synthetic small molecules. Here, we have studied neurohormone- Melatonin against in vitro Tau aggregation and observed its effect on membrane topology, tubulin network and Tau phosphorylation in Neuro2A and N9 cell lines. The aggregation and conformation of Tau was determined by ThT fluorescence and CD spectroscopy respectively. The morphology of Tau aggregates in presence and absence of Melatonin was studied by transmission electron microscopy. Melatonin was found to reduce the formation of higher order oligomeric structures without affecting the overall aggregation kinetics of Tau. Melatonin also modulates and helps to maintain membrane morphology, independent on tubulin network as evidenced by FE-SEM and immunofluorescence analysis. Overall, Melatonin administration shows mild anti-aggregation and cytoprotective effects. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Alzheimer's disease; Cell surface morphology; melatonin; Paired helical filaments; tau protein; Tauopathies

Interaction of Tau with the chemokine receptor, CX3CR1 and its effect on microglial activation, migration and proliferation - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (Cell and Bioscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease that leads to progressive loss of memory and dementia. The pathological hallmarks of AD include extracellular accumulation of amyloid-beta peptides forming senile plaques and intracellular accumulation of Tau oligomers and filamentous species. Tau is a microtubule-binding protein that stabilizes tubulin to form microtubules under physiological condition. In AD/ pathological condition, Tau detaches from microtubules and aggregates to form oligomers of different sizes and filamentous species such as paired helical filaments. Microglia are the resident brain macrophages that are involved in the phagocytosis of microbes, cellular debris, misfolded and aggregated proteins. Chemokine receptor, CX3CR1 is mostly expressed on microglia and is involved in maintaining the microglia in a quiescent state by binding to its ligand, fractalkine (CX3CL1), which is expressed in neurons as both soluble or membrane-bound state. Hence, under physiological conditions, the CX3CR1/CX3CL1 axis plays a significant role in maintaining the central nervous system (CNS) homeostasis. Further, CX3CR1/CX3CL1 signalling is involved in the synthesis of anti-inflammatory cytokines and also has a significant role in cytoskeletal rearrangement, migration, apoptosis and proliferation. In AD brain, the expression level of fractalkine is reduced, and hence Tau competes to interact with its receptor, CX3CR1. In microglia, phagocytosis and internalization of extracellular Tau species occurs in the presence of a chemokine receptor, CX3CR1 which binds directly to Tau and promotes its internalization. In this review, the pathophysiological roles of CX3CR1/fractalkine signalling in microglia and neurons at different stages of Alzheimer's disease and the possible role of CX3CR1/Tau signalling has been widely discussed.
Keywords: Alzheimer's disease; CX3CR1 receptor; Fractalkine; microglia; Neuron; Tau

Melatonin interacts with repeat domain of Tau to mediate disaggregation of paired helical filaments - Balmik, Abhishek Ankur; Das, Rashmi; Dangi, Abha; Gorantla, Nalini Vijay; Marelli, Udaya Kiran; Chinnathambi, Subashchandrabose (Biochimica Et Biophysica Acta-General Subjects, 2020)
Tau is the major neuronal protein involved in the stabilization of microtubule assembly. In Alzheimer's disease, Tau self-assembles to form intracellular protein aggregates which are toxic to cells. Various methods have been tried and tested to restrain the aggregation of Tau. Most of the agents tested for this purpose have limitations in their effectiveness and availability to neuronal cells. We have tested melatonin, a neurohormone secreted by pineal gland and a well-known anti-oxidant, for its ability to interact with the repeat domain of Tau using ITC and NMR. In aggregation inhibition and disaggregation studies of repeat Tau, melatonin was found to modulate the aggregation propensity of repeat Tau at a concentration of 5000 mu M and was more effective in dissolving preformed aggregates rather than acting as an aggregation inhibitor. However, there were no major conformational changes in Tau in presence of melatonin as observed by CD spectroscopy. On the basis of our findings, we are proposing a mechanism by which melatonin can interact with the repeat domain of Tau and exhibit its disaggregation effect.
Keywords: Alzheimer's disease; Disaggregation; melatonin; Paired helical filaments; tau protein; Tauopathies

Melatonin reduces GSK3 beta-mediated tau phosphorylation, enhances Nrf2 nuclear translocation and anti-inflammation - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (ASN Neuro, 2020)
Alzheimer's disease is a neuropathological condition with abnormal accumulation of extracellular Amyloid-beta plaques and intracellular neurofibrillary tangles of Microtubule-associated protein Tau (Tau) in the brain. In pathological conditions, Tau undergoes post-translational modifications such as hyperphosphorylation by the activity of cellular kinases, which eventually leads to protein aggregation in neurons. Melatonin is a neuro-hormone that is mainly secreted from the pineal gland and functions to modulate the cellular kinases. In our study, we have checked the neuroprotective function of Melatonin by MTT and LDH assay, where Melatonin inhibited the Tau aggregates-mediated cytotoxicity and membrane leakage in Neuro2A cells. The potency of Melatonin has also been studied for the quenching of intracellular reactive oxygen species level by DCFDA assay and caspase 3 activity. Melatonin was shown to reduce the GSK3 beta mRNA and subsequent protein level as well as the phospho-Tau level (pThr181 and pThr212-pSer214) in okadaic acid-induced Neuro2A cells, as observed by western blot and immunofluorescence assay. Further, Melatonin has increased the cellular Nrf2 level and its nuclear translocation as an oxidative stress response in Tauopathy. The Melatonin was found to induce pro- and anti-inflammatory cytokines levels in N9 microglia. The mRNA level of cellular kinases such as as-GSK3 beta, MAPK were also studied by qRT-PCR assay in Tau-exposed N9 and Neuro2A cells. The immunomodulatory effect of Melatonin was evident as it induced IL-10 and TGF-beta cytokine levels and activated MAP3K level in Tau-exposed microglia and neurons, respectively. Melatonin also downregulated the mRNA level of pro-inflammatory markers, IL-1 beta and Cyclooxygenase-2 in N9 microglia. Together, these findings suggest that Melatonin remediated the cytokine profile of Tau-exposed microglia, reduced Tau hyperphosphorylation by downregulating GSK3 beta level, and alleviated oxidative stress via Nrf2 nuclear translocation.
Keywords: Alzheimer’ Anti-inflammatory; GSK3β melatonin; microglia; neurodegeneration; Nrf2; s disease; Tau hyperphosphorylation

Phagocytosis of full-length Tau oligomers by Actin-remodeling of activated microglia - Das, Rashmi; Balmik, Abhishek Ankur; Chinnathambi, Subashchandrabose (Journal of Neuroinflammation, 2020)
Background Alzheimer's disease is associated with the accumulation of intracellular Tau tangles within neurons and extracellular amyloid-beta plaques in the brain parenchyma, which altogether results in synaptic loss and neurodegeneration. Extracellular concentrations of oligomers and aggregated proteins initiate microglial activation and convert their state of synaptic surveillance into a destructive inflammatory state. Although Tau oligomers have fleeting nature, they were shown to mediate neurotoxicity and microglial pro-inflammation. Due to the instability of oligomers, in vitro experiments become challenging, and hence, the stability of the full-length Tau oligomers is a major concern. Methods In this study, we have prepared and stabilized hTau40(WT) oligomers, which were purified by size-exclusion chromatography. The formation of the oligomers was confirmed by western blot, thioflavin-S, 8-anilinonaphthaalene-1-sulfonic acid fluorescence, and circular dichroism spectroscopy, which determine the intermolecular cross-beta sheet structure and hydrophobicity. The efficiency of N9 microglial cells to phagocytose hTau40(WT) oligomer and subsequent microglial activation was studied by immunofluorescence microscopy with apotome. The one-way ANOVA was performed for the statistical analysis of fluorometric assay and microscopic analysis. Results Full-length Tau oligomers were detected in heterogeneous globular structures ranging from 5 to 50 nm as observed by high-resolution transmission electron microscopy, which was further characterized by oligomer-specific A11 antibody. Immunocytochemistry studies for oligomer treatment were evidenced with A11(+) Iba1(high) microglia, suggesting that the phagocytosis of extracellular Tau oligomers leads to microglial activation. Also, the microglia were observed with remodeled filopodia-like actin structures upon the exposure of oligomers and aggregated Tau. Conclusion The peri-membrane polymerization of actin filament and co-localization of Iba1 relate to the microglial movements for phagocytosis. Here, these findings suggest that microglia modified actin cytoskeleton for phagocytosis and rapid clearance of Tau oligomers in Alzheimer's disease condition.
Keywords: Actin; activation; Alzheimer's disease; microglia; migration; neurodegeneration; Tau Oligomers; Tauopathy

Transition metal nickel prevents Tau aggregation in Alzheimer's disease - Gorantla, Nalini Vijay; Das, Rashmi; Balaraman, Ekambaram; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2020)
Alzheimer's disease is the leading cause of dementia, effecting majority of aged people worldwide. The multifaceted effectors of Alzheimer's disease primarily include Tau, amyloid-beta along with hyper activation of kinases, oxidative stress and mutations etc., makes it challenging to design therapeutics. Tau is a microtubule-associating protein, which is subjected to cellular stress resulting in the formation of neurofibrillary tangles, leading to loss of affinity for microtubules. This causes loss of microtubule stability and in turn alters axonal integrity. In the present work, emphasis towards understanding interaction of nickel with Tau was made. Metals such as iron, zinc, copper and lead etc., are known to modulate Tau conformation and enhance its aggregation. Our results showed the deliverance of Tau aggregation by nickel and its synthetic morpholine conjugate. Nickel prevents aggregation by inducing degradation of Tau as evidenced by SDS-PAGE and TEM. Nickel and the synthetic conjugate being non toxic to neuro2a cells and prevent Tau aggregation, might direct these complexes to overcome AD. (C) 2019 Published by Elsevier B.V.
Keywords: Aggregation; Alzheimer's disease; metals; Morpholine; Nickel chloride; Tau

Microglial remodeling of actin network by Tau oligomers, via G protein-coupled purinergic receptor, P2Y12R-driven chemotaxis - Das, Rashmi; Chinnathambi, Subashchandrabose (Traffic, 2021)
Alzheimer's disease (AD) is associated with age-related neurodegeneration, synaptic deformation and chronic inflammation mediated by microglia and infiltrated macrophages in the brain. Tau oligomers can be released from damaged neurons via various mechanisms such as exosomes, neurotransmitter, membrane leakage etc. Microglia sense the extracellular Tau through several cell-surface receptors and mediate chemotaxis and phagocytosis. The purinergic receptor P2Y12R recently gained interest in neurodegeneration for neuro-glial communication and microglial chemotaxis towards the site of plaque deposition. To understand the effect of extracellular Tau oligomers in microglial migration, the P2Y12R-mediated actin remodeling, reorientation of tubulin network and rate of migration were studied in the presence of ATP. The extracellular Tau species directly interacted with P2Y12R and also induced this purinoceptor expression in microglia. Microglial P2Y12R colocalized with remodeled membrane-associated actin network as a component of migration in response to Tau oligomers. As an inducer of P2Y12R, ATP facilitated the localization of P2Y12R in lamellipodia and filopodia during accelerated microglial migration. The direct interaction of extracellular Tau oligomers with microglial P2Y12R would facilitate the signal transduction in both way, directional chemotaxis and receptor-mediated phagocytosis. These unprecedented findings emphasize that microglia can modulate the membrane-associated actin structure and incorporate P2Y12R to perceive the axis and rate of chemotaxis in Tauopathy.
Keywords: actin remodeling; Alzheimer' chemotaxis; microglia; migration; s disease; Tau Oligomers

Neem derivatives inhibits tau aggregation - Nalini, Gorantla Vijay; Das, Rashmi; Mulani, Fayaj Alam; Thulasiram, Hirekodathakallu V.; Chinnathambi, Subashchandrabose (Journal of Alzheimer s Disease Reports, 2021)
Tau is a phosphoprotein with natively unfolded conformation that functions to stabilize microtubules in axons. Alzheimer's disease pathology triggers several modifications in tau, which causes it to lose its affinity towards microtubule, thus, leading to microtubule disassembly and loss of axonal integrity. This elicit accumulation of tau as paired helical filaments is followed by stable neurofibrillary tangles formation. A large number of small molecules have been isolated from Azadirachta indica with varied medicinal applications. The intermediate and final limonoids, nimbin and salannin respectively, isolated from Azadirachta indica, were screened against tau aggregation. ThS and ANS fluorescence assay showed the role of intermediate and final limonoids in preventing heparin induced cross-β sheet formation and also decreased hydrophobicity, which are characteristic nature of tau aggregation. Transmission electron microscopy studies revealed that limonoids restricted the aggregation of tau to fibrils; in turn, limonoids led to the formation of short and fragile aggregates. Both the limonoids were non-toxic to HEK293T cells thus, substantiating limonoids as a potential lead in overcoming Alzheimer's disease.

G-protein coupled purinergic P2Y12 receptor interacts and internalizes TauRD-mediated by membrane-associated actin cytoskeleton remodeling in microglia - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (European Journal of Cell Biology, 2022)
In Alzheimer’s disease, the microtubule-associated protein, Tau misfolds to form aggregates and filaments in the intra- and extracellular region of neuronal cells. Microglial cells are the resident brain macrophage cells involved in constant surveillance and activated by the extracellular deposits. Purinergic receptors are involved in the chemotactic migration of microglial cells towards the site of inflammation. From our recent study, we have observed that the microglial P2Y12 receptor is involved in phagocytosis of full-length Tau species such as monomers, oligomers and aggregates by actin-driven chemotaxis. This study shows the interaction of repeat-domain of Tau (TauRD) with the microglial P2Y12 receptor and the corresponding residues for interaction have been analysed by various in-silico approaches. In the cellular studies, TauRD was found to interact with microglial P2Y12R and induces its cellular expression confirmed by co-immunoprecipitation and western blot analysis. Furthermore, the P2Y12R-mediated TauRD internalization has demonstrated activation of microglia with an increase in the Iba1 level, and TauRD becomes accumulated at the peri-nuclear region for the degradation. Similarly, immunofluorescence microscopic studies emphasized that TauRD is phagocytosed by microglial P2Y12R via the membrane-associated actin remodeling as filopodia extension. Upon internalization, we have demonstrated the P2Y12R signaling-mediated degradation of accumulated TauRD by lysosomal pathway. Altogether, microglial P2Y12R interacts with TauRD and mediates directed migration and activation for its internalization and degradation.
Keywords: Alzheimer’s disease; Internalization; microglia; P2Y12R; Phagocytosis; Tau

G-protein coupled purinergic P2Y12 receptor interacts and internalizes Tau(RD)-mediated by membrane-associated actin cytoskeleton remodeling in microglia - Chidambaram, Hariharakrishnan; Das, Rashmi; Chinnathambi, Subashchandrabose (European Journal of Cell Biology, 2022)
In Alzheimer's disease, the microtubule-associated protein, Tau misfolds to form aggregates and filaments in the intra- and extracellular region of neuronal cells. Microglial cells are the resident brain macrophage cells involved in constant surveillance and activated by the extracellular deposits. Purinergic receptors are involved in the chemotactic migration of microglial cells towards the site of inflammation. From our recent study, we have observed that the microglial P2Y12 receptor is involved in phagocytosis of full-length Tau species such as monomers, oligomers and aggregates by actin-driven chemotaxis. This study shows the interaction of repeat-domain of Tau (Tau(RD)) with the microglial P2Y12 receptor and the corresponding residues for interaction have been analysed by various in-silico approaches. In the cellular studies, Tau(RD) was found to interact with microglial P2Y12R and induces its cellular expression confirmed by co-immunoprecipitation and western blot analysis. Furthermore, the P2Y12R-mediated Tau(RD) internalization has demonstrated activation of microglia with an increase in the Iba1 level, and Tau(RD) becomes accumulated at the peri-nuclear region for the degradation. Similarly, immunofluorescence microscopic studies emphasized that Tau(RD) is phagocytosed by microglial P2Y12R via the membrane-associated actin remodeling as filopodia extension. Upon internalization, we have demonstrated the P2Y12R signaling-mediated degradation of accumulated Tau(RD) by lysosomal pathway. Altogether, microglial P2Y12R interacts with Tau(RD) and mediates directed migration and activation for its internalization and degradation.
Keywords: Alzheimer's disease; Internalization; microglia; P2Y12R; Phagocytosis; Tau(RD)

Microglia degrade Tau oligomers deposit via purinergic P2Y12-associated podosome and filopodia formation and induce chemotaxis - Chinnathambi, Subashchandrabose; Das, Rashmi (Cell and Bioscience, 2023)
BackgroundTau protein forms neurofibrillary tangles and becomes deposited in the brain during Alzheimer's disease (AD). Tau oligomers are the most reactive species, mediating neurotoxic and inflammatory activity. Microglia are the immune cells in the central nervous system, sense the extracellular Tau via various cell surface receptors. Purinergic P2Y12 receptor can directly interact with Tau oligomers and mediates microglial chemotaxis via actin remodeling. The disease-associated microglia are associated with impaired migration and express a reduced level of P2Y12, but elevate the level of reactive oxygen species and pro-inflammatory cytokines.ResultsHere, we studied the formation and organization of various actin microstructures such as-podosome, filopodia and uropod in colocalization with actin nucleator protein Arp2 and scaffold protein TKS5 in Tau-induced microglia by fluorescence microscopy. Further, the relevance of P2Y12 signaling either by activation or blockage was studied in terms of actin structure formations and Tau deposits degradation by N9 microglia. Extracellular Tau oligomers facilitate the microglial migration via Arp2-associated podosome and filopodia formation through the involvement of P2Y12 signaling. Similarly, Tau oligomers induce the TKS5-associated podosome clustering in microglial lamella in a time-dependent manner. Moreover, the P2Y12 was evidenced to localize with F-actin-rich podosome and filopodia during Tau-deposit degradation. The blockage of P2Y12 signaling resulted in decreased microglial migration and Tau-deposit degradation.ConclusionsThe P2Y12 signaling mediate the formation of migratory actin structures like- podosome and filopodia to exhibit chemotaxis and degrade Tau deposit. These beneficial roles of P2Y12 in microglial chemotaxis, actin network remodeling and Tau clearance can be intervened as a therapeutic target in AD.
Keywords: Filopodia; microglia; migration; Podosome; Tau Oligomers

Tau aggregates improve the Purinergic receptor P2Y12-associated podosome rearrangements in microglial cells - Chinnathambi, Subashchandrabose; Das, Rashmi; Desale, Smita Eknath (Biochimica Et Biophysica Acta-Molecular Cell Research, 2023)
Alzheimer's disease (AD) is a progressive neurodegenerative disease that is associated with protein misfolding, plaque accumulation, neuronal dysfunction, synaptic loss, and cognitive decline. The pathological cascade of AD includes the intracellular Tau hyperphosphorylation and its subsequent aggregation, extracellular Amyloid-& beta; plaque formation and microglia-mediated neuroinflammation. The extracellular release of aggregated Tau is sensed by surveilling microglia through the involvement of various cell surface receptors. Among all, purinergic P2Y12R signaling is involved in microglial chemotaxis towards the damaged neurons. Microglial migration is highly linked with membrane-associated actin remodeling leading to the phagocytosis of extracellular Tau species. Here, we studied the formation of various actin structures such as podosome, lamellipodia and filopodia, in response to extracellular Tau monomers and aggregates. Microglial podosomes are colocalized with actin nucleator protein WASP, Arp2 and TKS5 adaptor protein during Tau-mediated migration. Moreover, the P2Y12 receptors were associated with F-actin-rich podosome structures, which signify the potential of Tau aggregates in microglial chemotaxis through the involvement of actin remodeling.
Keywords: Alzheimer `s disease; Filopodia; microglia; Podosome; Tau aggregates